Akuntabilitas Keuangan Pada Amal Usaha Muhammadiyah: Sebuah Pendekatan Kualitatif - Dwi Irawan; Mudrifah Mudrifah (Universitas Muhammadiyah Malang, 2022)
This study aims to reveal how the Muhammadiyah organization which has many Amal Usaha Muhammadiyah (AUM) reports its financial accountability. This study uses a qualitative descriptive approach in describing how accountability is in AUM. The informant of this research is the top management of AUM in Malang City. The results of this study indicate that accountability in AUM is based on the motto amar ma'ruf nahi munkar which is internalized within the management. In addition, the values of tajdid and ta'awun also form an accountable spirit in the management. Accountability for AUM is not only a form of social responsibility but there are elements of worship, trust, and devotion to Allah SWT. The contribution of this research is to contribute to the meaning of accountability which is based on the values of Muhammadiyah's struggle, which so far has been able to form an accountable of AUM management.